Optical Properties of S-doped and S, N Co-doped Graphene Quantum Dots and Application - Nga, Pham Thu; Hue, Trinh Thi; Huong, Nguyen Thi Mai; Thien, Phan Xuan; Hung, Le Xuan (VNU Journal of Science: Natural Sciences and Technology; Vol 40 No 4DO - 10.25073/2588-1140/vnunst.5757, 2024)
In recent years, carbon-based quantum dots, including carbon quantum dots (CQDs) and graphene quantum dots (GQDs), have been widely researched as new alternatives to conventional antibacterial agents. The structural characteristics and properties of the materials can also be tuned and controlled by changing the shape and size of the GQDs. Effective doping with heteroatoms can also tune the optical, electronic and electrochemical properties, etc., of GQDs. In this report, we study and synthesize sulfur (S)-doped graphene quantum dots and sulfur (S), nitrogen (N)-co-doped-graphene quantum dots using a simple method that requires minimal energy and is environmentally friendly. By controlling the absorption and luminescence spectra in the desired wavelength range, S, N-GQDs can easily be applied as biocides for common bacteria such as E. coli and S. aureus, also presented in this report.